INDONESIAN EFL STUDENTS’ USE OF TECHNOLOGIES FOR SELF-DIRECTED LEARNING IN ACCOMPLISHING ACADEMIC ENGLISH WRITING TASKS - Pasaribu, Joseph Bryant T.; manara, christine (Journal of English Language and Culture, 2024)
This study examines the use of technology for self-directed learning in accomplishing English writing tasks by Indonesian EFL students. The study are guided by two research questions: 1) How did university students use technologies to accomplish their academic English writing tasks?; 2) How did the use of technologies support university students’ self-directed learning (SDL)?A mixed-method approach was adopted in investigating these issues. Data were collected using questionnaire and in-depth interviews. The participants were students from three universities in Banten, South Jakarta, and Central Java. There were 51 students who filled out the questionnaire and only 13 of them were willing to be interviewed. The findings revealed that the majority of students used online apps to assist them in the process of drafting and editing their English writing tasks. The data indicate that knowledge on these online apps and how to utilize them are able to maintain their SDL in accomplishing their writing tasks. Their SDL is mostly influenced by their drive to obtain academic achievement. The findings also show that trainings on some technical skills and knowledge on editing apps are needed to maximize the students’ use of technology for their SDL.